HUBUNGAN PERAN KELOMPOK PETERNAK DENGAN PRODUKTIVITAS ANGGOTA KELOMPOK PETERNAK KAMBING DI KECAMATAN CILONGOK KABUPATEN BANYUMAS - Arif Dimas Novianto; Yusmi Nur Wakhidati; Krismiwati Muatip (Fakultas Peternakan Universitas Jenderal Soedirman, 2020)
Background. The aim of this research was to determine the role of the goat farmer group in Cilongok, Banyumas, the productivity of the goat farmer group members and to analyze in Cilongok, Banyumas, and the relationship between the role of the group and the productivity of the goat farmer group members in Cilongok, Banyumas. Materials and Methods. The research targets were the goat farmer group members in Cilongok, Banyumas. The research was a survey method with purposive sampling. The number of research respondent was 35 peoples. Results. The results showed the role of the farmer group as a learning class was categorized as high (80%), the role as a production unit was categorized as moderate (80%), and the role as a forum of cooperation was categorized as high (97%). The productivity of the goat farmer group members was classified as moderate, namely IDR 218.619-61.146 HKP/year. The relationship between the role of the group as a learning class, a forum of cooperation, a production unit, and the productivity of the goat farmer group members in Cilongok, Banyumas had a correlation of 0.167 (very weak), 0.104 (very weak), and 0.064 (very weak), with a significance value of 0.169, 0.277, and 0.358.